Evaluation of Normal and Nanolayer Composite Thermal Barrier Coatings in Fused Vanadate-Sulfate Salts at 1000°C - Mohammadreza Daroonparvar; Muhamad Azizi Mat Yajid; Noordin Mohd. Yusof; Hamid Reza Bakhsheshi-Rad; Mohammad Sakhawat Hussain; Esah Hamzah (Advances in Materials Science and Engineering)
Hot corrosion behavior of yttria stabilized zirconia (YSZ), YSZ/normal Al2O3, and YSZ/nano-Al2O3 coatings was investigated in the presence of molten mixture of Na2SO4 + V2O5 at 1000°C. Microstructural characterization showed that the creation of hot corrosion products containing YVO4 crystals and monoclinic ZrO2 is primarily related to the reaction between NaVO3 and Y2O3 during hot corrosion. The lowest amount of hot corrosion products was observed in YSZ as an inner layer of YSZ/nano-Al2O3 coating. Hence, it can be concluded that the presence of nanostructured Al2O3 layer over the conventional YSZ coating can considerably reduce the infiltration of molten corrosive salts into the YSZ layer during hot corrosion which is mainly related to the compactness of nanostructured alumina layer (including nanoregions) in comparison with normal alumina layer.